2021
DOI: 10.15537/smj.2021.42.7.20210040
|View full text |Cite
|
Sign up to set email alerts
|

Association between nonalcoholic fatty liver disease and Helicobacter pylori infection in Dali City, China

Abstract: To investigate whether gastric Helicobacter pylori (H. pylori( infection is associated with the progress of nonalcoholic fatty liver disease )NAFLD( in Dali city, China.Methods: One thousand and one hundred eighty-five adults who had visited a health examination center were enrolled. Nonalcoholic fatty liver disease and H. pylori infection were assessed by abdominal color ultrasound and 13 C-urea breath test, respectively. Serum lipid metabolic indices were compared between NAFLD subjects without and with H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The main characteristics of the observational studies included in the meta‐analysis are summarized in Table 1 for cross‐sectional studies and Table 2 for longitudinal studies. Twenty‐four studies 31–54 had a cross‐sectional design, whereas four studies 55–58 had a longitudinal design. Regarding the cross‐sectional studies (Table 1), twelve studies were carried out in China, two in Japan, two in the USA, two in South Korea, one in Austria, one in Bangladesh, one in Egypt, one in Greece, one in Guatemala and one in Iran, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the observational studies included in the meta‐analysis are summarized in Table 1 for cross‐sectional studies and Table 2 for longitudinal studies. Twenty‐four studies 31–54 had a cross‐sectional design, whereas four studies 55–58 had a longitudinal design. Regarding the cross‐sectional studies (Table 1), twelve studies were carried out in China, two in Japan, two in the USA, two in South Korea, one in Austria, one in Bangladesh, one in Egypt, one in Greece, one in Guatemala and one in Iran, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the forest plot and pooled estimates of the effect of H. pylori infection on the risk of MASLD in 24 cross‐sectional studies 31–54 . Overall, these studies included a total of 209 439 middle‐aged individuals (58% men; mean age 49 ± 8 years; BMI 25.3 ± 2.4 kg/m 2 ; ~95% from Asian countries), 27.5% ( n = 62 628) of whom had a diagnosis of MASLD and 38.2% had a diagnosis of prior or active H. pylori infection.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies involving 117,458 participants were included ( Table 1 ). This review contained two cohort studies ( 35 , 36 ), 17 cross-sectional studies ( 3 , 25 27 , 29 , 37 39 , 41 – 47 , 49 , 52 ), and six case-control studies ( 28 , 40 , 48 , 50 , 51 , 53 ). These studies were published between 2013 and 2021, three of which were conference abstracts ( 43 , 47 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, while Yan in Bali found that the infection of H. pylori represents an independent risk factor for NAFLD [ 25 ], Wang et al observed in an impressive study on 71,633 participants in China that the same infection was not a risk factor for liver function damage in patients with NAFLD (AST, p = 0.911; ALT, p = 0.237) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%